Development of The Thematic Teachbook Based on Contextual Teaching and Learning (CTL) Class II At MI Raudlatul Ulum Glagahwero Panti - Rahmawati, Nika Hadiya; Ubaidillah, Sofwan Roif (Pendidikan Islam Pascasarjana IAIN Jember, 2023)
ABSTRACT The development of thematic teaching materials that are more varied and in accordance with the daily lives of students and the environment where students live is not yet available at MI Raudlatul Ulum Glagahwero Panti, it is deemed necessary to develop contextual-based teaching materials, because they are able to provide a meaningful learning experience and involve an active role student. The objectives of developing these teaching materials are (1) to determine the validity of the contextual-based textbook with the theme